Copper(I) Iodide Mediated Synthesis of Carbohydrate-Based Terminal Allenes by ATA Reaction - Huang, Xin; Fu, Chunling; Ma, Shengming (Synthesis, 2014)
We have demonstrated two improved methods for the synthesis of carbohydrate-based terminal allenes from propargyl or homopropargyl glycosides. The reaction of propargyl or homopropargyl glycosides with paraformaldehyde (2.5 equiv) in the presence of copper(I) iodide (10 mol%) and diisopropylamine (1.8 equiv) or copper(I) iodide (50 mol%) and dicyclohexylamine (1.8 equiv) produces sugar-linked terminal allenes in 50–79% yield.
Keywords: copper(I) iodide; diisopropylamine; dicyclohexylamine; carbohydrates; allenes